Susceptibility map-weighted MRI can distinguish tremor-dominant Parkinson’s disease from essential tremor - Sungyang Jo; Chong Hyun Suh; Sangjin Lee; Jihyun Lee; MyungKi Yoon; Hwon Heo; Woo Hyun Shim; Sang Joon Kim; Eung Yeop Kim; Sun Ju Chung (Scientific Reports)
Abstract Distinguishing between Parkinson’s disease (PD) and essential tremor (ET) can be challenging sometimes. Although positron emission tomography can confirm PD diagnosis, its application is limited by high cost and exposure to radioactive isotopes. Patients with PD exhibit loss of the dorsal nigral hyperintensity on brain magnetic resonance imaging (MRI). Novel MRI-based approaches, including susceptibility map-weighted imaging (SMwI), allow visualization of the dorsal nigral hyperintensity at an increased resolution. Herein, we investigated the diagnostic accuracy of dorsal nigral hyperintensity evaluation on SMwI for distinguishing tremor-dominant PD from ET. Consecutive patients with tremor who underwent SMwI and were diagnosed with tremor-dominant PD or ET between July 2021 and July 2022 were enrolled. The dorsal nigral hyperintensity loss on SMwI was compared between the PD and ET groups. All 143 patients (100%) with tremor-dominant PD showed unilateral or bilateral dorsal nigral hyperintensity loss. Among 136 patients with ET, 131 (96.3%) exhibited an intact dorsal nigral hyperintensity, while 5 (3.7%) showed unilateral/bilateral dorsal nigral hyperintensity loss. SMwI discriminated between tremor-dominant PD and ET with a sensitivity and specificity of 100% and 96.3%, respectively. 18F-FP-CIT PET revealed normal findings in 4/5 patients with ET who had false-positive results on SMwI. These results indicate that dorsal nigral hyperintensity loss on SMwI could differentiate between tremor-dominant PD and ET with high accuracy.